2014
DOI: 10.1007/s11356-014-2762-6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic dietary exposure to pyrolytic and petrogenic mixtures of PAHs causes physiological disruption in zebrafish—part II: behavior

Abstract: In the last 10 years, behavior assessment has been developed as an indicator of neurotoxicity and an integrated indicator of physiological disruption. Polycyclic aromatic hydrocarbon (PAH) release into the environment has increased in recent decades resulting in high concentrations of these compounds in the sediment of contaminated areas. We evaluated the behavioral consequences of long-term chronic exposure to PAHs, by exposing zebrafish to diets spiked with three PAH fractions at environmentally relevant con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 88 publications
5
37
0
Order By: Relevance
“…Gesto et al (2006; 2008; 2009) demonstrated that PAH and oxy-PAH exposures altered the levels of DA and 5HT metabolites in the brain of rainbow trout. Moreover, other reports have associated zebrafish central nervous system (CNS) effects with exposure to various PAHs (Vignet et al 2014a; 2014b). In their studies, adult zebrafish which were developmentally exposed to individual PAHs or PAH mixtures, exhibited impaired locomotor activity, and increased anxiety compared to non-exposed fish.…”
Section: Resultsmentioning
confidence: 99%
“…Gesto et al (2006; 2008; 2009) demonstrated that PAH and oxy-PAH exposures altered the levels of DA and 5HT metabolites in the brain of rainbow trout. Moreover, other reports have associated zebrafish central nervous system (CNS) effects with exposure to various PAHs (Vignet et al 2014a; 2014b). In their studies, adult zebrafish which were developmentally exposed to individual PAHs or PAH mixtures, exhibited impaired locomotor activity, and increased anxiety compared to non-exposed fish.…”
Section: Resultsmentioning
confidence: 99%
“…Due to urban expansion and increased use of automobiles, the concentration of these compounds in aquatic environments is steadily increasing (Lima et al, 2003). Potential adverse impacts of PAHs include carcinogenesis, effects on the reproductive, neurologic, and immune systems, and developmental abnormalities (Arkoosh and Kaattari, 1991; Brown et al, 2016; Hawkins et al, 1990; Incardona et al, 2011; Johnson, 1988; Van Tiem and Di Giulio, 2011; Vignet et al, 2014a; Vignet et al, 2014b). In fish, the most notable adverse developmental effects occur due to bioactivation of PAHs via the aryl hydrocarbon receptor (AHR) pathway, disrupting normal cardiovascular development and resulting in deformities such as elongated “stringy” hearts, impaired heart looping, decreased blood flow, and pericardial effusion (Billiard et al, 2006; Incardona et al, 2004; Van Tiem and Di Giulio, 2011; Wassenberg and Di Giulio, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although the concentration of F is very low in fresh water (0.01-0.03 ppm), it is continuously increasing due to anthropogenic activities like rapid industrialization, use of fluoridated pesticides (CEPA, 1994) and municipal water discharges in rivers (Aguirre-Sierra et al, 2013). In the last ten years, behavior assessment has been developed as an indicator of neurotoxicity and an integrated indicator of physiological disruption (Vignet et al, 2014). Excessive F exposure is toxic not only for skeletal tissues (causing fluorosis), but also to the soft tissues including brain that may induce neurological defects and neurodegenerative disorders and mental retardation (see Podder et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The behavioral biomarkers are specially promoted due to two particular reasons-(1) they can be readily and non-invasively measured and (2) they can be more sensitive than physiological or structural biomarkers. Behavior can integrate multiple effects at the genetic, developmental, endocrine, neural and metabolic levels (Gerhardt 2007).There are several reports demonstrating the neurobehavioral and neurotoxic effects of different toxicants and environmental pollutants on zebrafish brain (Pereira et al, 2012;Vignet et al, 2014). Fish have also been used as models of human disorders in studies on compounds such as alcohol (MacPhail et al 2009).…”
Section: Introductionmentioning
confidence: 99%